PERLINDUNGAN HAK CIPTA PADA LAGU TERKAIT COVER VERSION DI YOUTUBE BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 - NIM. A1011191022, LIA TARANA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Human creativity that knows no boundaries has given birth to a new phenomenon that penetrates the world of music, namely cover versions of songs. Both the creator and copyright holder have exclusive rights to a song. Therefore, if there are parties who want to commercialize the song by making a cover version, that party needs permission or license from the creator or copyright holder. The formulation of the problem contained in this study is twofold, namely